Pengaruh Kompetensi, Kerjasama Tim, Dan Motivasi Terhadap Kinerja Satuan Kerja Bidang Hukum Kepolisian Daerah Sumatera Utara - Salpatore Simanjuntak; Sjahril Effendy P.; Hazmanan Khair (CERED Indonesia Institute, 2021)
The purpose of this study was to determine the effect of competence, teamwork, and motivation on the performance of the work unit in the Legal Division of the North Sumatra Regional Police partially and simultaneously. The data analysis technique used is multiple linear regression, t test (partial), F test (simultaneous) and R square test. From the test results that have been obtained, it can be concluded that partially competence has a positive and significant effect on performance, cooperation team has a positive and significant effect on performance, motivation does not has an effect and is not significant to the work unit's performance. Then by simultaneous competence, teamwork and motivation simultaneously have an effect positive and significant towards performance.